The Influence of Information Technology in the Learning Process during the Covid-19 Pandemic - David Saro (Engineering and Technology International Journal, 2022)
This study discusses the Covid-19 virus outbreak throughout the world which paralyzes all levels of society, including the world of education. Therefore, educational institutions need to find solutions so that teaching and learning activities can continue. The purpose of writing this article is to describe the role of education management information systems and information technology in the learning process during the Covid-19 pandemic. The method of writing this article is a literacy study. The results of the literacy study show that management information systems and information technology play a very important role in distance learning. Information technology acts as a container or learning tool, while information systems act as the brain in distance learning. However, before implementing distance learning, educational institutions need to provide several things such as distance learning infrastructure and ICT literacy for educators and students. These things are very important in achieving distance learning success.